Research on cloud native based distributed IoT operating system architecture - Nan CHEN; Jianjun ZHAO; Ping ZHONG; Yongjun HUANG; Tian CHEN (Dianxin kexue)
Complex application development, various types of IoT devices, diverse network technology and different types of IoT edge are the major problems of IoT.The novel concept and architecture of the cloud native based distributed IoT operating system were proposed with 8 core features, which extended the scope of operating system from IoT devices to the edge and cloud, followed the trend analysis of IoT industry and technology.The cloud native based distributed IoT operating system has been utilized to decoupling the complexity and differences of massive heterogeneous resources of cloud (platform), edge gateway, devices and the one-stop full life cycle support of intelligent Internet of things applications development, deployment and hosting.The research and development practices of CTWing OS as well as testing and applications were also introduced.